Simulated Effects of Soil Texture on Nitrous Oxide Emission Factors from Corn and Soybean Agroecosystems in Wisconsin. Issue 5 (1st September 2016) - Gaillard, Richard; Duval, Benjamin D.; Osterholz, William R.; Kucharik, Christopher J.
Abstract : Soil texture is known to have an influence on the physical and biological processes that produce N2 O emissions in agricultural fields, yet comparisons across soil textural types are limited by considerations of time and practicality. We used the DayCent biogeochemical model to assess the effects of soil texture on N2 O emissions from agriculturally productive soils from four counties in Wisconsin. We validated the DayCent model using field data from 2 yr of a long‐term (approximately 20‐yr) cropping systems trial and then simulated yield and N2 O emissions from continuous corn ( Zea mays L.) and corn–soybean ( Glycine max L.) cropping systems across 35 Wisconsin soil series classified as either silt loam, sandy loam, or loamy sand. Silt loam soils had the highest N2 O emissions of all soil types, exhibiting 80 to 158% greater mean emissions and 100 to 282% greater emission factors compared with loamy sand and sandy loam soils, respectively. The model predicts that for these soils under these cropping systems, denitrification constituted the majority of the N2 O flux only in the silt loam soils. However, across all soil textures, locations, and years, denitrification explained the most variation (74–98%) in total N2 O emissions. Our results suggest that soil texture is an important factor in determining a range of N2 O emission characteristics and is critical for estimating future N2 O emissions from agricultural fields. Core Ideas: Soil texture influences agricultural N2 O emissions and emission factors. Soil texture influences absolute and relative rates of nitrification and denitrification. Understanding soil texture effects is vital to estimating N losses via N2 O.